Cost-effectiveness analysis of toripalimab plus chemotherapy as the first-line treatment in patients with advanced non-small cell lung cancer (NSCLC) without EGFR or ALK driver mutations from the Chinese perspective - Zhou, Kexun; Shu, Pei; Zheng, Hanrui; Li, Qiu (Frontiers in Pharmacology, 2023)
Objectives: The results of a CHOICE-1 study demonstrated the superior efficacy of toripalimab (anti-PD-1 antibody) plus chemotherapy for patients with advanced non–small cell lung cancer (NSCLC), with a manageable safety profile. This study was performed to evaluate the economic value of this treatment for this patient population from the Chinese payer’s perspective. Materials and methods: Basic data were derived from the CHOICE-1 study. Markov models were developed to simulate the process of advanced NSCLC, including the progression-free survival (PFS), progressive disease (PD), and death in intention-to-treat (ITT) populations, as well as patients with squamous or non-squamous NSCLC. The cost was obtained from the local institution, and the value of utilities referred to previous studies. Monte Carlo simulations were performed to depict the probabilistic scatter plots of the incremental cost-effectiveness ratio (ICER) and acceptability curves, aiming to address the uncertainty of model inputs. Results: Compared with standard chemotherapy, toripalimab plus chemotherapy yields an ICER of $21,563 per quality-adjusted life year (QALY) in the ITT population. For patients with squamous NSCLC, comparing the combined therapy with chemotherapy led to an ICER of $18,369 per QALY, while the ICER was $24,754 per QALY in patients with non-squamous NSCLC. With the threshold of willingness to pay we set ($37,653 per QALY), toripalimab plus chemotherapy was cost-effective in these patient populations. Conclusion: For patients with advanced NSCLC, toripalimab plus chemotherapy was an optimal choice as first-line treatment, regardless of histology.